The weight of (the) matter: A new material feminist account of thin and fat oppressions. (September 2019) - Norman, Moss Edward; Moola, Fiona J.
Critical feminist approaches to eating disorders and "obesity" have recently come under criticism for relying too heavily on textual- and image-based analyses of health, identity and body weight, shape, and size. In this article, we examine qualitative interviews with self-identified anorexic and "obese" women using a new material feminist lens—particularly the work of Karen Barad—to see what this perspective contributes to conceptualizations of weight-based oppressions. In addition to outlining how the material world actively participates in ongoing processes of oppression, we also highlight how the body presses back, offering up potentially less oppressive processes of materialization. The article concludes on a cautiously optimistic note, pointing to how a new materialist framework may draw attention to micropolitical processes of becoming otherwise.